Thermal analysis on phase sensitive granisetron in situ forming implants - Evren ALGIN YAPAR & , Tamer BAYKARA (Journal of Applied Pharmaceutical Science, 2014)
In this study effect of gamma irradiation sterilization and storage conditions on thermal properties of phase sensitive granisetron in situ forming implant (ISFI) was investigated. ISFI was prepared by mixing Poly (DL-lactide-co-glycolide) (PLGA) with dimethylsulfoxide (DMSO) : propylene carbonate (PC) (1:1) solvent combination then granisetron HCl was added and homogenized. Following application of gamma irradiation, ISFI was stored at 25 °C for 4 months. Differential Scanning Calorimeter (DSC) measurements and Thermogravimetric Analysis-Differential Thermal Analysis (TGA-DTA) were carried out on fresh, irradiated and aged forms of granisetron ISFI. According to DSC, TGA and TGA-DTA thermograms and mass loss results application of gamma irradiation and storage of irradiated ISFI at 25 °C for 4 months have not significant effect on thermal stability of ISFI.
Keywords: In situ forming implant, Poly(DL-lactide-co-glycolide), Gamma irradiation sterilization, DSC, TGA-DTA, Stability.